The Grandson of Ben Sira - Cadbury, Henry Joel (Harvard theological review, 1955)
Users of Bible Translations and especially makers of them have reason to be interested in the grandson of Ben Sira. He is perhaps the earliest identified person of either species. He lived in Egypt twenty-one centuries ago having arrived there, as he tells us, “in the thirty-eighth year under Euergetes the King,” which is probably 132 B.C. That is of course too early to speak of a finished Bible, though he does know the law and the prophets and other books and knows them also in another tongue than Hebrew. It was another Hebrew book—what we call Ecclesiasticus—written by his own grandfather, that he himself translated into Greek. With other translations this was accepted into the Greek and Christian Bible and so has come down to us in the Septuagint, while its original in Hebrew was not ultimately so received in the Hebrew or Jewish Bible.